Optimal PID Controller Parameters for Nonlinear Gantry Crane System via MOPSO Technique - Jaafar, Hazriq Izzuan; Sulaima, Mohamad Fani; Mohamed, Zaharuddin; Jamian, Jasrul Jamani (2013)
This paper presents development of an optimal PID controller for controlling the nonlinear gantry crane system. The PSO with linear weight summation approach is implemented for finding optimal PID parameters. The effectiveness of variation weight summation is observed in order to find the optimal performances of system. The system dynamic model is derived using Lagrange equation. A combination of five parameters (PID and PD) controllers are utilized for positioning and oscillation control of the system. System responses including trolley displacement and payload oscillation are observed and analyzed. Simulation is conducted within Matlab environment to verify the performance of the controller. It is demonstrated that implementation of linear weight summation approach in controlling system is useful in order to find the required performances according to the needs and circumstances.